The Impact of Global Technology on Music Industry: The End of Copyright Regime - Hergianasari, Putri; Rumaksari, Atyanta Nika (JSW (Jurnal Sosiologi Walisongo), 2018)
On a global scale, the music industry is currently experiencing declining growth after a significant decline in profits. This phenomenon is common in the era of digital transformation. Based on the EU report (European Commission, 2017) that global technology is changing rapidly. This reflects the desire of humans to do more by finding opportunities to meet their needs. The internet is the starting point for why the global world is changing so fast. One example is the global economic sector. By using the internet, people can search for all digital entertainment content easily without filtering it out. Sharing files on the internet has a negative impact on the music industry's sales the old way. They demand the termination of sharing music through the internet such as Youtube. This paper analyzes the advantages and disadvantages of company-based file-sharing businesses in Indonesia. How the government takes advantage of this business and how the Indonesian music industry overcomes the effects of globalization